Islam in a Formal Legal Approach (Law); A Study of Theory and Implementation - Havis Aravik; Nur Khasanah; Achmad Irwan Hamzani (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
This article explained about Islam in formal legal approach (law). The function was to know how far the formal legal in Islamic perspective could be used as the reference to build Islam and answer the various new problems found in life, especially in Islamic society. Library research was used in this article. It was an approach that focused on the literature review and tried to provide an overview or description of the existing reality or what happened or the actual reality of the object under study. The results of this study showed that the Islamic studies approach was an interesting discourse in the Islamic sciences discourse. The formal legal approach was one of the models of approach in Islamic studies which examined various problems that arised in Islamic teachings and solved them from a formal legal (law) perspective. In the Indonesian context, a formal legal approach was applied in the form of legalization of Islamic law both formally and normatively, although this step was highly dependent on the political will of the government. Keywords: Islamic Studies, Formal Legal Approach, Islamic Law, Sharia, Fiqh AbstrakArtikel ini membahas tentang Islam dalam pendekatan legal formal (hukum) dengan tujuan untuk mengetahui sejauh mana pendekatan legal formal dalam perspektif Islam dapat dijadikan rujukan dalam membangun Islam dan menjawab berbagai permasalahan-permasalahan baru yang ditemukan dalam kehidupan masyarakat Islam. Artikel ini menggunakan pendekatan kepustakaan (library reseach) yakni sebuah pendekatan yang fokus terhadap kajian literatur dan berusaha memberikan gambaran atau mendeskripsikan kenyataan yang ada atau apa yang terjadi atau kenyataan sebenarnya pada obyek yang diteliti. Hasil penelitian ini memperlihatkan bahwa pendekatan studi Islam adalah wacana yang menarik dalam diskursus ilmu-ilmu keislaman. Pendekatan legal formal (hukum) merupakan salah satu model pendekatan dalam studi Islam yang meneropong berbagai permasalahan-permasalahan yang muncul dalam ajaran Islam dan menyelesaikannya dalam perspektif legal formal (hukum). Dalam konteks keindonesiaan pendekatan legal formal diberlakukan dalam bentuk legalisasi hukum Islam baik secara yuridis formal maupun normatif, walaupun langkah tersebut sangat tergantung dengan political will dengan pemerintah. Kata Kunci: Studi Islam, Pendekatan Legal formal, Hukum Islam, Syariah, Fikih